2010
DOI: 10.1093/her/cyp068
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy among adults: a study from Turkey

Abstract: Patients' health literacy is increasingly recognized as a critical factor affecting health communication and outcomes. We performed this study to assess the levels of health literacy by using Rapid Estimate of Adult Literacy in Medicine (REALM) and Newest Vital Sign (NVS) instruments. Patients (n = 456) at a family medicine clinic completed in-person interviews, REALM and NVS tests which were translated into the Turkish language by translation-back translation process. Additional questions regarding demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
106
3
21

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(139 citation statements)
references
References 23 publications
9
106
3
21
Order By: Relevance
“…The data analysis revealed that most of the individuals presented good functional health literacy, corroborating other studies with samples from different age groups and using other previously validated evaluation instruments, such as the Rapid Estimate of Adult Literacy in Medicine (REALM) (11) and the Test of Functional Health Literacy -TOFHLA (12,13) , which have shown adequate functional health literacy scores for most individuals. A study that used the Newest Vital Sign -NVS (11) as an instrument of evaluation verified adequate functional health literacy in about one third of the sample evaluated.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The data analysis revealed that most of the individuals presented good functional health literacy, corroborating other studies with samples from different age groups and using other previously validated evaluation instruments, such as the Rapid Estimate of Adult Literacy in Medicine (REALM) (11) and the Test of Functional Health Literacy -TOFHLA (12,13) , which have shown adequate functional health literacy scores for most individuals. A study that used the Newest Vital Sign -NVS (11) as an instrument of evaluation verified adequate functional health literacy in about one third of the sample evaluated.…”
Section: Discussionsupporting
confidence: 85%
“…A study that used the Newest Vital Sign -NVS (11) as an instrument of evaluation verified adequate functional health literacy in about one third of the sample evaluated. It is worth mentioning that the majority of individuals in such samples were female, a percentage that is similar to the present study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This finding was inconsistent with previous studies suggesting that less educated adults were more likely to rate their oral health as fair ⁄ poor (Atchison & Gift, 1997;Finlayson et al, 2010;Gift et al, 1998;Matthias et al, 1995). This discrepancy can be explained by the fact that Turkish adults with lower education level have lower levels of health literacy (Ozdemir et al, 2010). Recent studies suggest that health literacy is associated with educational attainment in self-rated health and in regular dental attendance pattern among older adults (Bennett et al, 2009).…”
Section: Discussionmentioning
confidence: 66%
“…Ancak, bu çalışmada yer alan gençlerin NVS puanları, Özdemir ve arkadaşlarının çalışmasında ulaşılanların yaklaşık 2 katı kadardır. 11 Bu durum, katılımcıların farklı yaş gruplarında olmaları kadar bizim çalışmadaki gençlerin hepsinin hem lise mezunu, hem de üniversite sınavında tıp ve hemşirelik fakültelerini kazanacak kadar başarılı olmaları önemli bir etkendir. Bu gençlerin girdikleri sınavlar nedeniyle, matematiksel işlemlere daha yatkın ve seçtikleri alan itibariyle de sağlık alanına ve bu alanda kullanılan terimlere yakın ve ilgili olmalarına bağlanabilir.…”
Section: Bulgularunclassified